Prediction of complications of chronic duodenal ulcer using the method of determining the ratio of the level of melatonin receptors in the mucosa - Z. Kh. Osmanov; D. Yu. Semenov; A. P. Bogdanov; L. E. Koloscova; A. V. Sokolov; V. B. Vasilyev (Вестник хирургии имени И.И. Грекова)
Treatment of complications of peptic ulcer disease is an urgent problem in abdominal surgery due to the high prevalence of bleeding (19-57) and perforations (3-14 cases per 100,000 population).The objective of the study was to assess the possibility of predicting the development of ulcerative disease complications determining the ratio of the level of melatonin receptors (MT1/MT2) in the duodenal mucosa.Methods and materials. 56 patients with different course of peptic ulcer disease were examined. All patients underwent esophagogastroduodenoscopy with biopsy of the bulb duodenum. Biopsies were analyzed on a flow cytometer. The results were statistically processed.Results. The ratio of melatonin receptors MT1/MT2 significantly differed in the group of patients with bleeding and in the group with perforation. During the statistical analysis, it was found that at a value of MT1/MT2≥1,7, it is possible to assume the development of complications in the patient in the form of perforation or bleeding.Conclusion. The method of determining the ratio of melatonin receptors (MT1/MT2) in patients with complicated peptic ulcer disease can be used for prediction the risk of complications.